2018
DOI: 10.1021/jacs.8b08165
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Transformation of Boron Nitride Catalysts under Oxidative Dehydrogenation Conditions

Abstract: Hexagonal boron nitride (h-BN) and boron nitride nanotubes (BNNT) were recently reported as highly selective catalysts for the oxidative dehydrogenation (ODH) of alkanes to olefins in the gas phase. Previous studies revealed a substantial increase in surface oxygen content after exposure to ODH conditions (heating to ca. 500 °C under a flow of alkane and oxygen); however, the complexity of these materials has thus far precluded an in-depth understanding of the oxygenated surface species. In this contribution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
179
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(204 citation statements)
references
References 47 publications
18
179
0
Order By: Relevance
“…For example, hexagonal BN in conditions of ODH, which is covered with understoichiometric and amorphous BO x (OH) y layer, shows highly fluxional behavior . Furthermore, solid‐state NMR shows that the majority of the interface structure is covered by the inactive boron oxide . Hence, it is minority species that must govern this highly selective conversion of propane to propene.…”
Section: Implications Of the Ensemble Nature And Dynamic Fluxionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hexagonal BN in conditions of ODH, which is covered with understoichiometric and amorphous BO x (OH) y layer, shows highly fluxional behavior . Furthermore, solid‐state NMR shows that the majority of the interface structure is covered by the inactive boron oxide . Hence, it is minority species that must govern this highly selective conversion of propane to propene.…”
Section: Implications Of the Ensemble Nature And Dynamic Fluxionalitymentioning
confidence: 99%
“…79 Furthermore, solid-state NMR shows that the majority of the interface structure is covered by the inactive boron oxide. 80 Hence, it is minority species that must govern this highly selective conversion of propane to propene. Therefore, fluxionality and structural diversity emerging under reaction conditions must be taken into account in theoretical descriptions of the catalytic interface.…”
Section: Implications Of the Ensemble Nature And Dynamic Fluxionalimentioning
confidence: 99%
“…[32][33][34] But the realization of this future economy relies on the development of ah ighly efficient catalytic system for the reversibility and high selectivity of LOHC, [35] especially the N-ethylcarbazole (NEC) and dodecahydro-N-ethylcarbazole (12H-NEC) cycle systems. [34] Considering the highly efficient catalytic activity of h-BN in oxidative dehydrogenation of propane (ODHP) for olefin production, [11,12,37,38] we envisioned that the crystalline nanoporous h-BNNS obtained in this study could act as an efficient metal-free catalyst for the dehydrogenation of 12H-NEC.I ndeed, taking NEC-12H as am odel substrate (Figure 4), a74% yield of NEC was obtained using the as-prepared crystalline h-BNNS as the catalyst at al ow reaction temperature (120 8 8C). [34] Considering the highly efficient catalytic activity of h-BN in oxidative dehydrogenation of propane (ODHP) for olefin production, [11,12,37,38] we envisioned that the crystalline nanoporous h-BNNS obtained in this study could act as an efficient metal-free catalyst for the dehydrogenation of 12H-NEC.I ndeed, taking NEC-12H as am odel substrate (Figure 4), a74% yield of NEC was obtained using the as-prepared crystalline h-BNNS as the catalyst at al ow reaction temperature (120 8 8C).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…h-BN structures are characterized by their excellent thermal and chemical stability,a nd unique electronic and optical properties,w hich are widely applied in the field of energy storage and transformation. [11,12] Although both bulk h-BN and BNNT exhibited analogous product distributions,B NNT showed ar ate of propane consumption more than one order of magnitude higher than that of h-BN,p artially because of the higher surface area of BNNT (97 m 2 g À1 )relative to bulk h-BN (16 m 2 g À1 ), and thus as uperior mass transfer effect during the catalytic process. [2,[8][9][10] To date,H ermans et al reported that bulk h-BN and boron nitride nanotubes (BNNT) exhibited unique and highly efficient catalytic properties for the oxidative dehydrogenation of propane,resulting in great selectivity to olefins (79 % propene and 12 %e thene at 14 %p ropane conversion).…”
mentioning
confidence: 99%
“…We recently employed solid-state NMR spectroscopy to investigate boron nitride materials and demonstrated that the oxidized phase on used boron nitride catalysts can be denoteda sB 2 (OH) 2x O 3Àx (0 x 2), which contains the active site for ODH. [26] During reactionk inetic studies of hBN-catalyzed ODH, it was revealed that the O 2 partial pressure (P O 2 )s ignificantly influenced the observed product distribution. [24] Performing the oxidation of n-butane at low P O 2 results in ap roduct distribution that consists mainly of cracking products (e.g.,m ethane, ethylene, propylene).…”
Section: Introductionmentioning
confidence: 99%